(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Several studies evaluated the physical fitness profiles of people in different categories, including college students in India. However, relatively little information is available about physical fitness profiles of the Indian school students, whatever little information that is available on physical fitness in on the Indian school students documented outside Karnataka.